2013
DOI: 10.1242/jcs.128876
|View full text |Cite
|
Sign up to set email alerts
|

The architectural relationship of components controlling mast cell endocytosis

Abstract: SummaryEukaryotic cells use multiple routes for receptor internalization. Here, we examine the topographical relationships of clathrin-dependent and clathrin-independent endocytic structures on the plasma membranes of leukemia-derived mast cells. The high affinity IgE receptor (FceRI) utilizes both pathways, whereas transferrin receptor serves as a marker for the classical clathrin-mediated endocytosis pathway. Both receptors were tracked by live-cell imaging in the presence or absence of inhibitors that estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
1
15
0
1
Order By: Relevance
“…These clathrincoated sites are unlike those observed by EM in other mammalian cell types (Dambournet et al, 2018;Scott et al, 2018;Sochacki et al, 2014). However, there is some similarity between the raised clathrin structures we observe in B cells and the structures that form on mast cells in response to FCeRI clustering (Aggeler and Werb, 1982;Cleyrat et al, 2013;Wilson et al, 2002). There is overlap in the BCR and FCeRI signaling cascades (Siraganian et al, 2010), and the morphological similarity we observe in the receptors' endocytic structures suggests that there may be commonalities in their mechanisms of internalization as well.…”
Section: Discussionmentioning
confidence: 48%
“…These clathrincoated sites are unlike those observed by EM in other mammalian cell types (Dambournet et al, 2018;Scott et al, 2018;Sochacki et al, 2014). However, there is some similarity between the raised clathrin structures we observe in B cells and the structures that form on mast cells in response to FCeRI clustering (Aggeler and Werb, 1982;Cleyrat et al, 2013;Wilson et al, 2002). There is overlap in the BCR and FCeRI signaling cascades (Siraganian et al, 2010), and the morphological similarity we observe in the receptors' endocytic structures suggests that there may be commonalities in their mechanisms of internalization as well.…”
Section: Discussionmentioning
confidence: 48%
“…Stable transfectants were obtained using the appropriate selective agent as described in Cleyrat et al[53]…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, two independent groups have more recently reported that siRNA-mediated clathrin depletion does not affect antigen-dependent FcεRI internalization (65, 75), demonstrating that engaged FcεRI complexes can efficiently take an alternative route for endocytosis if the clathrin pathway is inhibited.…”
Section: The Ubiquitin Pathway As Endocytic Route Of Fc Receptorsmentioning
confidence: 99%